Rice plant parasitic nematodes in the Northern and Atlantic Regions of Costa Rica. - Guzmán-Hernández, Tomás de Jesús; Hernández-Villalobos, Silvia; Varela-Benavides, Ingrid; Durán-Mora, Joaquín; Montero-Carmona, Wayner (Agronomía Mesoamericana, 2011)
The objective of this stud ywas to identify the plant parasitic nematodes associated with the rice crop in the Northern and Atlantic regions of Costa Rica. Population growth of the main genuses was described and quantified using mathematical models, for which tables of incidence were constructed. A total of 14 rice fields in the Northern region and 15 rice fields in the Atlantic region were sampled between 2006 and 2009. Nematodes from soil and roots were extracted, then numbers of nematodes of each plant-feeding genus were counted. Pratylenchus was the genus with the greatest population density in the Northern region(17 024 individuals/100 g of root) followed by Meloidogyne(10 343 individuals/100 g of root). In the Atlantic Region the genus with the greatest population density was Meloidogyne(18 806 individuals/100 g of root) followed by Pratylenchus(8535 individuals/100 g of root). Other genera identified in the samples were Helicotylenchus, Tylenchorhynchus,Tylenchus and Criconemoides. The mathematical model thatbest represented the population of Pratylenchus was linear(R2 = 0.99), while the population growth of Meloidogynefitted an exponential model (R2 = 0.91)